2021
DOI: 10.5194/hess-25-447-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a land surface model at a water-limited site: implications for land surface contributions to droughts and heatwaves

Abstract: Abstract. Land surface models underpin coupled climate model projections of droughts and heatwaves. However, the lack of simultaneous observations of individual components of evapotranspiration, concurrent with root-zone soil moisture, has limited previous model evaluations. Here, we use a comprehensive set of observations from a water-limited site in southeastern Australia including both evapotranspiration and soil moisture to a depth of 4.5 m to evaluate the Community Atmosphere-Biosphere Land Exchange (CABL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 111 publications
0
23
0
Order By: Relevance
“…Beyond this particular eucalypt plantation, our findings suggest that projections from models relying on SWC observations in the upper soil layers will overestimate drought impacts on tree species with the ability to mobilize water from deep soil (e.g., Humphrey et al, 2018;Uddin et al, 2018). Therefore, including the ability of vegetation to access deep soil water reservoirs could improve dy- Thus far, stand-scale simulation models tend to better describe tree water uptake than DGVMs (e.g., Mu et al, 2021;Ukkola et al, 2016).…”
Section: Mobilizing Water From Deep Soil Layers Ameliorates Drought Stressmentioning
confidence: 91%
See 2 more Smart Citations
“…Beyond this particular eucalypt plantation, our findings suggest that projections from models relying on SWC observations in the upper soil layers will overestimate drought impacts on tree species with the ability to mobilize water from deep soil (e.g., Humphrey et al, 2018;Uddin et al, 2018). Therefore, including the ability of vegetation to access deep soil water reservoirs could improve dy- Thus far, stand-scale simulation models tend to better describe tree water uptake than DGVMs (e.g., Mu et al, 2021;Ukkola et al, 2016).…”
Section: Mobilizing Water From Deep Soil Layers Ameliorates Drought Stressmentioning
confidence: 91%
“…Additionally, six levels of precipitation were considered: +5%, +0%, −5%, −10%, −15%, and −20% of annual precipitation; no seasonal variations were considered. Although long-term deep soil water dynamics are strongly linked to precipitation patterns (Berg et al, 2017;Berg & Sheffield, 2018 and references therein;Seneviratne et al, 2010), there are still important uncertainties about the dynamics of such soil water reservoirs in SW Australia, mostly driven by the impact of vegetation (Mu et al, 2021). Therefore, for each precipitation reduction scenario, we assumed a linear decrease in S deep proportional to the reduction in precipitation.…”
Section: Climate Sensitivity Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…This study addressed a high soil evaporation bias that has also been observed in other models' simulations of grasslands, wetlands, and forests, but especially in regions with sparse vegetation (Sun and Verseghy, 2019;Decker et al, 2017;Kauwe et al, 2017;Mu et al, 2021). The empirical formulation by Merlin et al (2011) of the soil evaporation efficiency reduces simulated high rates of ground evaporation, particularly in spring, which avoided overdrying the 0-10 cm soil layer and greatly underestimating summer soil temperature, LE, and GPP, particularly in years with less summer rainfall.…”
Section: Tundra-atmosphere Water Vapour Exchangementioning
confidence: 96%
“…The parameters η and κ are PFT-specific (Table 2). The parameter values for trees, crops, and grasses are based on Lüdeke et al (1994), while η and κ for shrubs were estimated from values of C s , C R , and C L for shrub tundra (Nobrega and Grogan, 2007;Grogan and Chapin, 2000;Murphy et al, 2009;Wang et al, 2016), resulting in the same κ values as for grasses but higher η (Table 2). (Lafleur and Humphreys, 2018) and 200 to 300 mm of precipitation on average (ECG, 2012).…”
Section: Model Modificationsmentioning
confidence: 99%